Training and Assistance in Utilizing Huma for Fitness and Health for the Outer Baduy Community, Ciboleger - Dena Widyawan; Mochamad Derry Prasaja; Rizki khoirul Yakin; Sul Abidin; Weny Widyawati Bastaman (I-Com: Indonesian Community Journal, 2026)
The Outer Baduy community in Ciboleger faces an increasing risk of degenerative diseases due to changing lifestyles and lack of structured physical activity. The huma, their traditional stilt house, holds untapped potential as a fitness training tool. This community service activity aims to improve the knowledge, skills, and physical fitness of residents through training and assistance in utilizing the huma structure for exercise. Methods included health education, training in bodyweight-based huma exercise techniques, demonstrations, and group mentoring for two months. Evaluation was carried out through knowledge questionnaires, fitness tests (flexibility, cardiorespiratory endurance, handgrip strength), and observation. Results showed significant improvements in knowledge (from an average of 45.3 to 85.7) and all fitness components (p<0.05). Three huma exercise groups were formed and are actively training. Residents reported reduced back pain complaints and increased stamina. In conclusion, locally-wisdom-based training is effective and sustainable for improving the health status of indigenous communities.